Principles of waveform diversity and design - Wicks, Michael C.; Mokole, Eric L.; Blunt, Shannon D.; Schneible, Richard S.; Amuso, Vincent J. (SciTech Publishing, 2010)
The book reviews developments in the following fields: waveform diversity paradigms; multi-mission systems; long-range active sensing; distributed aperture sensing; distributed aperture communications; remote sensing; spectrum management; waveform design; chaotic waveforms; imaging waveforms; and matched illumination.